Book Review: The Arte Militaire. The Application of 17th Century Military Manuals to Conflict Archaeology by Warwick Louth - Thit Birk Petersen (EXARC, 2017)
The book consists of the rewritten essay of a master thesis. The author got his master's degree as a battlefield and conflict archaeologist from the Centre of Battlefield Archaeology at University of Glasgow founded by Professor Dr. Tony Pollard in 2006. I myself have studied at the Centre of Battlefield Archaeology back in 2007, and it was a pleasure to dive back into my old field. It was especially a pleasure as this book is very well written and well researched.